Pathogenetic characterization of a Micrococcus luteus strain isolated from an infant - Shi, Xiaolu; Qiu, Shuxiang; Ji, Liyin; Lu, Huiqun; Wu, Shuang; Chen, Qiongcheng; Zou, Xuan; Hu, Qinghua; Feng, Tiejian; Chen, Shiting; Cui, Wenkai; Xu, Shiqin; et al. (Frontiers in Pediatrics, 2023)
Purpose: To explore the clinical characteristics of Micrococcus luteus bloodstream infection in an infant and characterize the phenotype and genotype of the isolated strains, as well as seek suitable infection models for assessing virulence.Methods: Clinical data was collected from an infant patient diagnosed with M. luteus bloodstream infection. Metagenomic sequencing was performed on the isolated blood sample. The strain was isolated and underwent mass spectrometry, biochemical tests, antibiotic susceptibility assays, and whole-genome sequencing. The Galleria mellonella infection model was used to assess M. luteus virulence.Results: Patient responded poorly to cephalosporins, but recovered after Linezolid treatment. Metagenomic sequencing identified M. luteus as the predominant species in the sample, confirming infection. They were identified as M. luteus with a high confidence level of 98.99% using mass spectrometry. The strain showed positive results for Catalase, Oxidase, and Urea tests, and negative results for Mannose, Xylose, Lactose, Mannitol, Arginine, and Galactose tests, consistent with the biochemical profile of M. luteus reference standards. M. luteus susceptibility to 15 antibiotics was demonstrated and no resistance genes were detected. Predicted virulence genes, including clpB, were This is a provisional file, not the final typeset article associated with metabolic pathways and the type VI secretion system. The infection model demonstrated dose-dependent survival rates.The infant likely developed a bloodstream infection with M. luteus due to compromised immunity. Although the isolated strain is sensitive to cephalosporin antibiotics and has low pathogenicity in infection models, clinical treatment with cephalosporins was ineffective. Linezolid proved to be effective, providing valuable guidance for future clinical management of such rare infections.